Transient Receptor Potential (TRP) Channels in Drug Discovery: Old Concepts & New Thoughts - Susan Huang; Arpad Szallasi (Pharmaceuticals, 2017)
2017 marks the 20th anniversary of the molecular cloning by David Julius and colleagues (1997) of the long sought-after capsaicin receptor, now known as TRPV1 (Transient Receptor Potential Vanilloid 1) [1]. This seminal discovery has opened up a “hot” new field of basic research and launched drug discovery efforts into the large family (by the latest count 28 mammalian members, 27 in humans) of TRP ion channels [2]. Indeed, it took less than a decade for the first potent, small molecule TRPV1 antagonists to enter phase 1 clinical trials [3]. Yet, despite the large amount of resources that has been invested in TRPV1 research, there are currently no TRPV1-targeted drugs in phase 3 clinical trials. In this special issue of Pharmaceuticals, we aim to capture the progress in the TRP channel field over the past twenty years, with 15 articles covering a variety of TRP channels and potential relevant disease states and applications.